Chinese Academic Views on Shang Yang Since the Open-Up-and-Reform Era. Issue 2 (2nd April 2016) - Pines, Yuri; Defoort, Carine
ABSTRACT: The Book of Lord Shang attributed to Shang Yang (d. 338 BCE) is one of the most controversial products of ideological debates in pre-imperial China (pre-221 BCE). Forty years ago, Li Yu-ning summarized previous rounds of debates that peaked with the Shang Yang fervor of the early 1970s. The present article takes over where she ended, further exploring trends in studies of the Book of Lord Shang since the Open-up-and-Reform Era (1978–). The paper shows that despite a clear tendency of depoliticization of these studies, scholars are still deeply influenced by the tradition of using the figure of Shang Yang as a foil in contemporary political debates. In their evaluation of Shang Yang's legacy, many contemporary Chinese scholars continue to use traditional views, but also modern ideas such as the "rule of law, " "progress, " "evolution, " "dialectic, " or the Marxist theory of distinct social stages. They all contribute to the ongoing relevance of Lord Shang to current China.